2006
DOI: 10.1007/s10533-005-0712-6
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Soil Organic Matter: Association with Minerals or Chemical Recalcitrance?

Abstract: Soil organic matter (OM) can be stabilized against decomposition by association with minerals, by its inherent recalcitrance and by occlusion in aggregates. However, the relative contribution of these factors to OM stabilization is yet unknown. We analyzed pool size and isotopic composition ( 14 C, 13 C) of mineral-protected and recalcitrant OM in 12 subsurface horizons from 10 acidic forest soils. The results were related to properties of the mineral phase and to OM composition as revealed by CPMAS 13 C-NMR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
504
7
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 753 publications
(549 citation statements)
references
References 80 publications
35
504
7
3
Order By: Relevance
“…As soil Al or Fe oxides are generally associated with clay+fi ne silt fraction contents (Zinn et al, 2007), our results showed a correlation of clay+fi ne silt fraction with SOC ( Figure 1A) and with macroaggregates ( Figure 1F). The formation of organo-mineral complexes which protect SOC from biodegradation (Wiseman and Püttemann, 2005;Mikutta et al, 2006) and the adsorption of SOC on the high specifi c surface area resulting from Al-Fe substitution (Barthes et al, 2008) might explained this positive relationship between clay+fi ne silt contents and SOC content ( Figure 1A). Therefore, these results confi rm SOC physicochemical stabilization for SOC accumulation mechanisms in such soils.…”
Section: Resultsmentioning
confidence: 99%
“…As soil Al or Fe oxides are generally associated with clay+fi ne silt fraction contents (Zinn et al, 2007), our results showed a correlation of clay+fi ne silt fraction with SOC ( Figure 1A) and with macroaggregates ( Figure 1F). The formation of organo-mineral complexes which protect SOC from biodegradation (Wiseman and Püttemann, 2005;Mikutta et al, 2006) and the adsorption of SOC on the high specifi c surface area resulting from Al-Fe substitution (Barthes et al, 2008) might explained this positive relationship between clay+fi ne silt contents and SOC content ( Figure 1A). Therefore, these results confi rm SOC physicochemical stabilization for SOC accumulation mechanisms in such soils.…”
Section: Resultsmentioning
confidence: 99%
“…In two comparisons, NaOCl appears to cause less mineral alteration and yield an older OM fraction than does HCl (Mikutta et al 2006;Zimmermann et al 2007). These approaches use chemical reactivity of organic matter as a proxy for readiness to microbial degradation, rather than attempting to separate material of different chemistry per se.…”
Section: Fractionation Of Soil Organic Mattermentioning
confidence: 96%
“…Within the profile, the δ 13 C of bulk soil increases by 1-3‰ with increasing depth and decreasing particulate SOM. Comparisons of 100 y old and modern soil profiles shows that the increase in 13 C with depth is not due to fossil fuel effects (Torn et al 2002), but there is ongoing discussion regarding whether these trends are caused by microbial discrimination or selective preservation of plant compounds (Dijkstra et al 2006;Mikutta et al 2006) and resolution of these questions may be difficult using only natural abundance stable isotopes and non-manipulated systems.…”
Section: Natural Abundance Stable Carbon Isotopes ( 13 C)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent direct observations indicate the OC in the subsurface exists in smaller, simpler molecular structures than originally thought based on bulk extractions, and that often these reactive molecules persist in sedimentary systems much longer than previously believed (10,11). This different perspective suggests that the molecular properties do not in themselves control reaction rates but OC decomposition rates are affected by ecosystem properties such as nutrient limitation, energy scarcity, or carbon bioavailability due to physical limitation such as reactions with mineral surfaces (12)(13)(14). These recent observations suggest that sedimentary organic matter or older OC pools may also be available for microbial respiration.…”
mentioning
confidence: 98%